Dimension-six anomalous tqγ couplings in γγ collision at the LHC - S.C. İnan (Nuclear Physics B, 2015)
We have investigated the flavor changing top quark physics on the dimension-six anomalous tqγ (q=u,c) couplings through the process pp→pγγp→ptq¯p at the LHC by considering different forward detector acceptances. In this paper, we have also examined the effects of top quark decay. The sensitivity bounds on the anomalous couplings and t→qγ branching ratio have been obtained at the 95% confidence level for the effective Lagrangian approach. Besides, we have investigated the effect of the anomalous couplings on single top quark spin asymmetry.